Spinal analgesia for cancer pain - Raphael, Jon (Henry Stewart Talks, 2009)
Pain management continuum, The blood-brain barrier, CNS distribution of spinal and systemic analgesics, Selective spinal analgesia, Physiological rationale, Epidural vs. intrathecal, Pharmacology, Opioids, Local anesthetics, a2 adrenergic agonists, Ziconotide, Procedures
Reviewed at 2019/12/04